Unmasking the history of 3C 293 with LOFAR sub‐arcsecond imaging. Issue 9 (7th December 2021) - Kukreti, Pranav; Morganti, Raffaella; Shimwell, Timothy W.; Morabito, Leah K.; Beswick, Robert J.; Brienza, Marisa; Hardcastle, Martin J.; Sweijen, Frits; Jackson, Neal; Miley, George K.; Moldon, Javier; Oosterloo, Tom; et al.
Abstract: Active galactic nuclei show episodic activity, which can be evident in galaxies that exhibit restarted radio jets. These restarted jets can interact with their environment, leaving signatures in the radio spectral energy distribution. Tracing these signatures requires resolved spectral index measurements over a broad frequency range. We present such a study for the radio galaxy 3C 293. Using the International Low Frequency Array Telescope (ILT), we probe spatial scales as fine as ∼0.2″ at 144 MHz and to constrain the spectrum, we combine these data with Multi‐Element Radio Linked Interferometer Network and Very Large Array archival data at frequencies up to 8.4 GHz. In the inner lobes (∼2 kpc), we detect the presence of a compact steep spectrum (CSS) source with a spectral turnover at ∼225 MHz, caused by free‐free absorption from the rich surrounding medium. We find evidence of interaction of the lobes with the rich interstellar medium of the host galaxy. The outer lobes (extending up to ∼100 kpc) have a remarkably uniform spatial distribution of spectral index and only mild spectral curvature (of ∼0.2). Overall, it appears that 3C 293 has gone through multiple (two to three) epochs of activity. This study adds 3C 293 to the new sub‐group of restarted galaxies with short interruption time periods (≲1 Myr). This is the first time a spatially resolved study has been performed that simultaneously studies a young CSS source as well as the older outer lobes at such low frequencies.